Plana Memora: Dekontekstualisasi Wujud Karya Seni Rupa - Rahim, Muhamad Ali; Amiarsa, Chandra Ghaisani (Universitas Komputer Indonesia, 2020)
PLANA MEMORA is a visual work created to respond to the shifting phenomena of contemporary aesthetic discourse. Beginning with the idea of ​​'celebration' will fade the exclusivity of art leading to a pattern of continuity of creation. The conceptual purpose is the manifestation of the location of the authentic-specific personality spirit of postmodern art creative works; in the simplicity of visualization, philosophical elements can be found that require effort to understand their 'depth'. The practical aim is to offer patterns of unconventional work creation techniques, and their visualization becomes an alternative display of two-dimensi works of art. The form of PLANA MEMORA is like a brief note, made to give a simple and quick warning of daily activities plans. It is handwritten using a ballpen on a piece of paper. The rationale is that postmodern artworks characterize the familiar and intense closeness of the creators' daily lives. This reinforces the author that two-dimensi works of art are no longer (merely) about illustrations, representations of real/dreamy nature, imagination or ending in the composition of color splashes, which ends only show the skill of hand techniques in making it. To support the representation of contemporary artworks, the author designed PLANA MEMORA as a response to the ongoing shift in aesthetic discourse symptoms, as a decontextual manifestation of the form of visual works. This work is not an illustration of events, more accurately called the continuity of symptoms itself. Although it may be similar to documentation, but more work (plan) today and the future.